Diet and hygiene practices influence morbidity in schoolchildren living in Schistosomiasis endemic areas along Lake Victoria in Kenya and Tanzania-A cross-sectional study. - Iman Mohamed; Safari Kinung'hi; Pauline N M Mwinzi; Isaac O Onkanga; Kennedy Andiego; Geoffrey Muchiri; Maurice R Odiere; Birgitte Jyding Vennervald; Annette Olsen (Public Library of Science (PLoS), 2018)
Since 2011, cohorts of schoolchildren in regions bordering Lake Victoria in Kenya and Tanzania have been investigated for morbidity caused by Schistosoma mansoni infection. Despite being neighbouring countries with similar lifestyles and ecological environments, Tanzanian schoolchildren had lower S. mansoni prevalence and intensity and they were taller and heavier, fewer were wasted and anaemic, and more were physical fit compared to their Kenyan peers. The aim of the present study was to evaluate whether diet and school-related markers of socioeconomic status (SES) could explain differences in morbidity beyond the effect of infection levels.Parasitological and morbidity data from surveys in 2013-2014 were compared with information on diet and school-related markers of SES collected in 2015 using questionnaires. A total of 490 schoolchildren (163 Kenyans and 327 Tanzanians) aged 9-11 years provided data. A higher proportion of Tanzanian pupils (69.4%, 95% CI: 64.3-74.5) knew where to wash hands after toilet visits compared to Kenyan pupils (48.5%, 95% CI: 40.9-56.1; P<0.0005). Similar proportions of children in the two countries ate breakfast, lunch and dinner, but the content of the meals differed. At all three meals, a higher proportion (95% CI) of Tanzanian pupils consumed animal proteins (mostly fish proteins) compared to their Kenyan peers (35.0% (28.3-41.7) vs. 0%; P<0.0005 at breakfast; 69.0% (63.9-74.1) vs. 43.6% (35.8-51.4); P<0.0005 at lunch; and 67.2% (62.1-72.3) vs. 53.4% (45.8-61.0); P = 0.003 at dinner). Multivariable analyses investigating risk factors for important morbidity markers among individuals revealed that after controlling for schistosome and malaria infections, eating animal proteins (fish) and knowing where to wash hands after toilet visits were significant predictors for both haemoglobin levels and physical fitness (measured as VO2 max).These results suggest that the differences in morbidity may be affected by factors other than S. mansoni infection alone. Diet and hygiene practice differences were associated with health status of schoolchildren along Lake Victoria in Kenya and Tanzania.Trials Registration numbers: ISRCT 16755535 (Kenya), ISRCT 95819193 (Tanzania).